Uncommon presentation of a patient with hereditary haemorrhagic telangiectasia - I. N. Walmsley; V. Ratnamalala; J. Indrakumar (Asian Journal of Internal Medicine, 2024)
Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant disorder. It is clinically characterised by telangiectasia, recurrent epistaxis, and visceral vascular lesions. We report a case of HHT without a significant family history. A 16-year-old girl presented with multiple episodes of bleeding, including uncommon sites, over a period of ten months. She denied a family history of bleeding. Her clinical examination was unremarkable. Investigations including basic and second-line coagulation tests were normal. Subsequently multiple telangiectasias in the right nasal septum and capillary dilatation in the bladder wall were detected. According to Curaçao diagnostic criteria, a diagnosis of HHT was made. As her bleeding was self-limiting, follow up was arranged to monitor complications.